Alpha-Mangostin and Gamma-Mangostin Isolated from Mangosteen (Garcinia mangostana L.) as Promising Candidates against SARS-CoV-2: A Bioinformatics Approach - Arif Nur Muhammad Ansori (Institute of Medico-legal Publications Pvt Ltd, 2022)
The world is endangered by the COVID‐19 pandemic caused by SARS‐CoV‐2, people are dying in thousands every day, and without an actual treatment, it seems that bringing this global health problem to a quit is impossible. Natural products have been in constant use since ancient times and are proven by time to be effective. Medicinal plants from Indonesia may lead to the discovery of the novel drugs. Mangosteen or Garcinia mangostana L. is a native tropical fruit from Southeast Asia and is known to contain bioactive compounds. Interestingly, the main xanthone derivatives are alpha-mangostin and gamma-mangostin, these compounds have a variety of pharmacological activities such as antiviral activity. In summary, this study showed potential pharmacological benefits of alpha-mangostin and gamma-mangostin isolated from mangosteen against SARS-CoV-2. Thus, mangosteen exhibits as a valuable plant and a candidate for future drug development to fight SARS-CoV-2. However, further trials, such as in vitro and in vivo evaluation, are needed to prove the validity of these findings